Respostas

A melhor resposta!
2014-04-02T18:19:27-03:00
f(x)=Q(x)*D(x)+R(x) \\ f(x)=F(x)=(x^4+x^2+3x+1)*(x-2)+3 \\ 
f(x)=x^5-2x^4+x^3-2x^2+3x^2-6x+x-2+3 \\ f(x)=x^5-2x^4+x^3+x^2-5x+1

Este é o polinômio, agora é só dividi-lo por x-1

f(x)=x⁵-2x⁴+x³+x²-5x+1              x+1
      -x⁵-x⁴                                   x⁴-3x³+4x²-3x-2
       / -3x⁴+x³
          3x⁴+3x³
           /    4x³+x²
               -4x³-4x²
                 /  -3x²-5x
                     3x²+3x
                       /  -2x+1
                           2x+2
                             /  3
                    

3 5 3